Constructions of nationhood in secession debates related to Mthwakazi Liberation Front in Bulawayo's Chronicle and Newsday newspapers in 2011 - Ndlovu, Mphathisi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2013)
This study investigates the constructions of nationhood in two Bulawayo newspapers, the Chronicle and Newsday. Against the backdrop of the emergence of a secessionist movement, Mthwakazi Liberation Front (MLF), this research examines the discourses of nationhood in the secessionist debates raging in these two newspapers. This study is premised on a view that nationhood constructions cannot be understood outside the broader context in which these newspapers are embedded. Accordingly, it traces the roots and resurgence of Matabeleland separatist politics, exploring the political-historical forces that have shaped a distinctive Ndebele identity that poses a threat to the one, indivisible Zimbabwean national identity. Further, the study situates Matabeleland separatist politics within the broader African secessionist discourse challenging the post-colonial nation-building project on the continent. Informed by Hall's (1992, 1996) constructivist approach to identity, it considers national identities as fragmented, multiple and constantly evolving. Thus, this study is framed within Hall's (1997) constructivist approach to representation, as it examines the constructions of nationhood in and through language. The study uses qualitative research methods, as it examines the meanings of nationhood in key media texts. Informed by Foucault's discourse theory, this research employs critical discourse analysis (CDA) to analyse 12 articles from the two newspapers. The findings confirm that the representations of nationhood in the two newspapers are influenced by their position within the socio-political context. The state-owned Chronicle legitimates the unitary state discourse advocated by ZANU PF. On the other hand, Newsday's representations are informed by the discourses of the opposition political parties and civil society that challenge the dominant nation-building project. Thus, within this paper, secession and devolution emerge as alternative imaginaries that contest the authoritarian discourse of nationhood
Keywords: Newspapers; Bulawayo; Matabeleland; Zimbabwe; Chronicle; Newsday; Secession; Devolution; Nationhood; Ndebele; Ethnic identity; Mthwakazi Liberation Front; Mthwakazi Liberation Front -- Zimbabwe; Mass media and nationalism -- Research -- Zimbabwe; Bulawayo (Zimbabwe) -- Newspapers; Matabeleland (Zimbabwe) -- History -- Autonomy and independence movements; Matabeleland (Zimbabwe) -- Social conditions; Zimbabwe -- Social conditions